EVALUATION OF ALBENDAZOLE AGAINST SHEEP STRONGYLES IN FARMS OF KARNATAKA STATE BY DIFFERENT IN VITRO TESTS - S.C. Kumar; C. Renukaprasad; Placid. E. D’Souza; B.S. Pradeep (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Faecal samples of 264 sheep from 4 different sheep farms belonging to three different districts of Karnataka were screened to note the incidence of gastrointestinal nematodes. It was found that 93% of the sheep harboured strongyle infection. The faecal egg counts were found to be light to moderate. The in vitro egg hatch assay was employed to assess the resistance of strongyles in 4 sheep farms. The ED50 value for albendazole ranged between 2.5μg/ml to 6.9 μg/ ml which indicated the resistance of the gastrointestinal nematodes. All the samples were also subjected to another in vitro test, viz., larval development assay. The values ranged between 3-2μg to 4.2μg / ml which also indicated the development of resistance to albendazole. Larval paralysis assay confirmed the development of resistance to albendazole.